Indian economic: its development experience - Misra, S.K.; Puri, V. K. (Bombay, 1992)
1991-92 has been an eventful year for the Indian economy. First the rupee was devalued by 18 per cent in July 1991 and this was followed by a new liberalised export - import policy which considerably opened up the economy and introduced freely trade able EXIM scrips. Then a new liberalised industrial policy was announced on 24 July 1991 which virtually abolished industrial licensing, scrapped the assets limit for MRTP companies, diluted the role of public sector and opened up new vistas for the private sector in addition to adopting a more liberal approach to foreign investment and technology. This was followed by more concessions to foreign companies in November 1991 and January 1992 making FERA almost redundant. The Budget for 1992-93 presented by the Finance Minister on 29 February 1992 carried the process of liberalisation still further by proposing a number of 'structural changes'. These structural changes include making the rupee partially convertible, scrapping the EXIM scrip, reducing the floor on bank interest by one per cent, slashing the statutory liquidity ratio on incremental domestic liabilities of commercial banks, bringing most imports under OGL and abolishing government control over capital issues. The new five year export-import policy announced on 31 March 1992 (co-terminus with the Eighth Five Year Plan) gave a further push to the liberalisation process by freely allowing imports of all items except a negative list, decanalising a large number of raw materials including non ferrous metals and further liberalising import of capital goods against export obligation.
Keywords: Economic